2015
DOI: 10.1016/j.tips.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Designing selective inhibitors for calcium-dependent protein kinases in apicomplexans

Abstract: Apicomplexan parasites cause some of the most severe human diseases including malaria (caused by Plasmodium), toxoplasmosis, and cryptosporidiosis. Treatments are limited by lack of effective drugs and development of resistance to available agents. By exploiting novel features of protein kinases in these parasites, it may be possible to develop new treatments. We summarize here recent advances in identifying small molecule inhibitors against a novel family of plant-like, calcium-dependent kinases that are uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 96 publications
0
42
0
Order By: Relevance
“…Phylogenetic analysis based on the kinase domains suggested that they are close to CDPK4 and CDPK7, and they were named CDPK4B (TgME49_240390) and CDPK7A (TgME49_237860), respectively (see Fig. S1 in the supplemental material), as previously discussed (15). Analyses of domain structures of all CDPKs in T. gondii were performed using an online software PROSITE (http: //prosite.expasy.org/), which suggested that these CDPKs can be classed into two groups based on their domain structure.…”
Section: Sequence and Expression Analyses Of Noncanonical Cdpks In Tmentioning
confidence: 54%
See 2 more Smart Citations
“…Phylogenetic analysis based on the kinase domains suggested that they are close to CDPK4 and CDPK7, and they were named CDPK4B (TgME49_240390) and CDPK7A (TgME49_237860), respectively (see Fig. S1 in the supplemental material), as previously discussed (15). Analyses of domain structures of all CDPKs in T. gondii were performed using an online software PROSITE (http: //prosite.expasy.org/), which suggested that these CDPKs can be classed into two groups based on their domain structure.…”
Section: Sequence and Expression Analyses Of Noncanonical Cdpks In Tmentioning
confidence: 54%
“…CDPKs likely arose by fusion of a calmodulin-like domain containing four EF hands, a structural feature first described in parvalbumin and that is responsible for calcium binding, followed by their diversification in plants and protists (10). The fact that CDPKs are not found in animal cells, combined with the findings that some of them are essential, has made them attractive targets for development of inhibitors (15).…”
Section: -Isoleucine [I]-lysine [K]-lysine [K]) Kinases In Plasmodiummentioning
confidence: 99%
See 1 more Smart Citation
“…Support for this model is provided by inhibition of PKG with Compound 1 (15,17), and selective inhibition of CDPK1 with pyrazolopyrimidine inhibitors (8,47). Both classes of compounds offer promise for development of alternative therapeutics, given the essential nature of these kinases and the potent and specific inhibition offered by these respective chemical scaffolds (48,49). Evidence that PKG may enhance Ca 2ϩ release via increased production of IP 3 links these two pathways (19).…”
Section: Discussionmentioning
confidence: 99%
“…3 and SI Appendix, Tables S32 and S33). The kinase domain from all known Ca 2+ sensor kinases belongs to the CAMK group of kinases, whereas this uncharacterized protein belongs to the tyrosine kinase-like (TKL) class of kinases (72,73). The genes encoding homologous proteins are present on many other red algal genomes, including Chondrus, Cyanidioschyzon, and Galdieria, but appear to be absent from all other characterized eukaryotic genomes.…”
Section: Significancementioning
confidence: 99%